Prediction of severe pre-eclampsia in low-risk women - N. I. Frolova; T. E. Belokrinitskaya; K. A. Kolmakova (Фундаментальная и клиническая медицина, 2021)
Aim. To find the predictors of severe pre-eclampsia in women without any established risk factors.Materials and Methods. We consecutively recruited 200 pregnant women (100 with severe pre-eclampsia and 100 with uncomplicated pregnancy and successful delivery). Criteria of inclusion were age from 18 to 35 years, absence of significant comorbid conditions (cardiovascular diseases, autoimmune diseases, metabolic disorders, and kidney diseases), absence of family history and past medical history of pre-eclampsia and thromboembolism, singleton pregnancy, and body mass index in the first trimester < 35 kg/m2 . We assessed allele and genotype distribution across several gene polymorphisms (ADD1-1378G>T, AGT704T>C, AGT-521C>T, AGTR1-1166A>C, AGTR2-1675G>A, NO3-894G>C, and NO3-786T>C) potentially associated with severe pre-eclampsia.Results. We found that the combination of AGTR2-1675АA and eNOS3-786СC polymorphisms (p = 0.04), bacteriuria (p < 0.001), acute respiratory infections (p = 0.011) and acute vulvovaginitis in second and third trimesters (p = 0.013), smoking (p < 0.001), and past medical history of abortions (p = 0.017) were risk factors of severe pre-eclampsia.Conclusions. Predictors of severe pre-eclampsia revealed in this study can be used in the development of personalised prognostication during pregnancy in patients without conventional risk factors of pre-eclampsia.